Human and porcine Taenia solium infections in Mozambique: Identifying research priorities - Afonso, S.M.S.; Vaz, Y.; Neves, L.; Pondja, A.; Dias, G.; Willingham, Arve Lee; Vilhena, M.; Duarte, P.C.; Jost, Christine; Noormahomed, E.V. (Cambridge University Press, 2011)
The objective of this paper is to critically review and summarize available scientific and lay literature, and ongoing studies on human and porcine cysticercosis in Mozambique to identify knowledge gaps and direct immediate and long-term research efforts. Data on the spatial distribution and prevalence of the disease in human and swine populations are scarce and fragmented. Human serological studies have shown that 15–21% of apparently healthy adults were positive for cysticercosis antibodies or antigen, while in neuropsychiatric patients seroprevalence was as high as 51%. Slaughterhouse records indicate a countrywide occurrence of porcine cysticercosis, while studies have shown that 10–35% of pigs tested were seropositive for cysticercosis antibodies or antigen. Current research in Mozambique includes studies on the epidemiology, molecular biology, diagnosis and control of the disease. Future research efforts should be directed at better understanding the epidemiology of the disease in Mozambique, particularly risk factors for its occurrence and spread in human and swine populations, documenting the socio-economic impact of the disease, identifying critical control points and evaluating the feasibility and epidemiological impact of control measures and development of local level diagnostic tools for use in humans and swine.